Differences in anthropometric and physical performance characteristics between U17, U19, and Senior Irish female international football players - Doyle, B.; Browne, D.; Horan, D. (International Journal of Sports Science & Coaching, 2021)
This study aimed to compare the anthropometric physical performance characteristics of Irish female international footballers at U17, U19, and Senior age groups. Fifty-five (U17, n =24, U19, n =21, Senior, n = 10) female international football players participated in this study. The subjects underwent anthropometric measurements (height and body mass) and physical performance tests countermovement jump (CMJ), reactive strength index (RSI), 10-m, 20-m, 30-m linear sprint, and yo-yo intermittent recovery test level 1 (YYIR1). No significant differences were identified between any age groups for the anthropometric measures of height and body mass. Concerning the physical tests, senior players displayed greater CMJ scores in comparison with the U17 (P = 0.040). Senior players also possessed higher levels of reactive strength with large effect sizes present (ES = 0.83 - 0.92) in comparison to all age groups. No significant differences were identified between any of the age groups across the 10-m, 20-m, 30-m, and rolling 20-m linear speed assessments. Senior players covered the greatest distance in the YYIR1 (P = 0.0001) versus the U19 and U17. These results indicate there was no difference in the anthropometric profile of the age groups assessed. However, differences in physical performance characteristics were present between age groups, thus suggesting improvements in lower limb power and aerobic endurance are achievable in adulthood as players physically mature.